Using Powerpoint Media to Learning Outcomes Theme 4 Sub-theme 2 Learning 6 in Class III Students of SD Negeri 1 Karanganyar Academic Year 2020/2021 - Pancawati, Yuliana Yustina (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
The purpose of this research was to improve learning outcomes in theme 4 sub-theme 2 learning 6 grade III elementary schools with a powerpoint media. The research conducted was a Classroom Action Research (PTK) with three cycles, with each cycle consisting of two meetings. The stages of each cycle are planning, implementing, observing and reflecting. Each meeting is carried out a pre test and post test to determine the progress of students. In the first cycle the students who completed after carrying out the post test were 35%. In the second cycle students who completed after carrying out the post test were 60%. In the third cycle students who completed after carrying out the post test were 90%. These results indicate that powerpoint media can improve student interest and learning outcomes, especially grade III theme 4 sub-theme 2 learning 6 at SDN 1 Karanganyar.